Legal Statement of Deed of Inheritance Made by a Notary Who Does Not Include All Heirs in the Distribution of Inheritance - Fernandus H Pardede (Indonesian Journal of Advanced Research, 2023)
Humans as social beings have their own goals and interests. However, humans cannot fulfill their needs alone, so other humans are needed to help each other, interact and have mutual dependence on one another in order to fulfill both physical and mental needs. Basically, the continuity of marriage cannot always be established, this is due to death. This death has consequences for the heirs, such as his family related to the assets left by the heir but also for other parties who still have a legal relationship with the person who died, such as creditors.